Optimalisasi Penempatan dan Besaran Shunt Capacitor pada Fasilitas Interkoneksi Generator Distribusi (Studi Kasus di PT PLN (Persero) Rayon Dolok Sanggul) - Darma Wijaya (Universitas Syiah Kuala, 2016)
The existence of distributed generation (DG) has improved voltage regulation, but it reverses power factor and network losses on Dolok Sanggul distribution system. The operation scheme and the lenght of interconnection facility of DG have caused the increase reactive power flow on distribution system. The increase in reactive power flow could be compensated by the installment of shunt capacitor. Optimal Capacitor Placement ETAP Power Station with the objective function is to minimize the cost of distribution system was used to search the placement and the size of shunt capacitor in the interconnection facility of DG. After the installment of shunt capacitor, the cost of distribution system can be saved Rp 2,092,403,071,- (US 152,208) in Peak Load Time (WBP) and Rp 8,390,300,625,- (US 610,337) in Outside Peak Load Time (LWBP) in the five-year period.